Penanganan Perkara Penyalahgunaan Narkotika Dengan Pendekatan Keadilan Restoratif Perspektif Hukum Pidana Islam - Avivah Firisqi Leksono; Fery Dona (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
The significant increase in narcotics criminal cases in the city of Surakarta in the last three years and the situation of overcapacity in the Surakarta Detention Center have prompted the Surakarta District Prosecutor's Office to take action to resolve alternative criminal cases, namely restorative justice. Based on this background, this paper aims to examine how narcotics abuse cases are handled using a restorative justice approach at the Surakarta District Prosecutor's Office and how it is viewed from the Islamic Criminal Law perspective. This research is a qualitative field research with an empirical juridical approach. Primary data was obtained directly from the Surakarta District Prosecutor's Office in the form of case data and interviews, while secondary data was obtained from books, journal articles and scientific works related to research. To collect the data, interviews and documentation were carried out. The data obtained was then analyzed using the data analysis method according to Miles and Huberman, namely data reduction, data display, and data conclusion. The results of the research explain that the handling of narcotics abuse cases with restorative justice at the Surakarta District Prosecutor's Office has been successfully implemented in two narcotics abuse cases. Meanwhile, from the perspective of Islamic criminal law, the provisions for handling narcotics abuse cases with restorative justice are not found in the Al-Quran or Sunnah, so that the Authorities are responsible for deciding the punishment that is deemed appropriate for the case, which is usually called ta'zir.